High-sensitivity c-reactive protein and gamma-glutamyl transferase levels are synergistically associated with metabolic syndrome in community-dwelling persons - Kawamoto, Ryuichi (BioMed Central, 2010)
BACKGROUND: Metabolic syndrome (MetS) is associated with an increased risk of major cardiovascular events. Increased high-sensitivity C-reactive protein (hsCRP) levels are associated with MetS and its components. Changes in gamma-glutamyl transferase (GGT) levels in response to oxidative stress are also associated with MetS, and the levels could be modulated by hsCRP. METHODS: From a single community, we recruited 822 men (mean age, 61 ± 14 years) and 1,097 women (63 ± 12 years) during their annual health examination. We investigated whether increased hsCRP and GGT levels are synergistically associated with MetS and insulin resistance evaluated by Homeostasis of model assessment of insulin resistance (HOMA-IR). RESULTS: Of these subjects, 141 men (17.2%) and 170 women (15.5%) had MetS. Participants with MetS had a higher hsCRP and GGT level than those without MetS in both genders, and the HOMA-IR increased significantly in correlation with an increase in hsCRP and GGT. In men, the adjusted odds ratios (95% confidence interval) for MetS across tertiles of hsCRP and GGT were 1.00, 1.69 (1.01-2.80), and 2.13 (1.29-3.52), and 1.00, 3.26 (1.84-5.78) and 6.11 (3.30-11.3), respectively. In women, the respective corresponding values were 1.00, 1.54 (0.92-2.60), and 3.08 (1.88-5.06), and 1.00, 1.70 (1.04-2.79) and 2.67 (1.66-4.30). The interaction between increased hsCRP and GGT was a significant and independent determinant for MetS and insulin resistance in both genders. CONCLUSIONS: These results suggested that higher CRP and GGT levels were synergistically associated with MetS and insulin resistance, independently of other confounding factor in the general population.